THE DISCURSIVE CONSTRUCTIONS OF PROTESTS AGAINST GOVERNMENT POLICIES BY INSTAGRAM POSTS - Herlin Triana; Vivi Indriyani; Rohaidah Haron; Delsy Arma Putri (UIN Raden Mas Said Surakarta, 2025)
Social media has become an influential arena for expressing critical perspectives and resistance toward socio-political challenges. Its role in accelerating the circulation of information and shaping public responses is particularly evident in political contexts. This study investigates the implicit and explicit meanings conveyed in Instagram posts from the @serikatpekerjakampus account, employing a pragmatic discourse framework to examine how meanings are constructed and communicated. Using a descriptive qualitative approach, the research identifies speech acts and implicatures that appear within the multimodal discourse of the posts. The findings reveal that expressive illocutionary acts and imperative implicatures dominate communication strategies. These results indicate that while textual and visual elements apply different modes of meaning-making, they converge toward the same communicative objectives. The multimodal analysis further demonstrates that symbols, idioms, and images serve as semiotic resources of the protests against government policies and reinforce the posts’ critical stance. The implications of these findings highlight Instagram as a strategic platform for fostering critical discourse with strong pragmatic effects on shaping public opinion. In addition, this research positions social media as a significant subject of inquiry within critical linguistics and multimodal studies. Ultimately, the presence of digital criticism illustrates the tangible impact of social media practices on policy-making processes in contemporary socio-political landscapes.